HUBUNGAN SENAM HAMIL DENGAN RUPTUR PERINEUM PADA SAAT PERSALINAN DI PMB DINCE SAFRINA PEKANBARU - Rita Afni; Octa Dwienda Ristica (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Childbirth is the process of releasing the product of conception (fetus and placenta) which has been quite months or has been able to live outside the womb through the birth canal, with or without assistance. Labor often results in tearing of the perineum. The incidence of perineal rupture in maternal mothers in the world in 2015 there were 2.7 million cases, where this figure is estimated to reach 6.3 million in 2050. Based on a preliminary survey conducted by researchers at PMB Dince Safrina SST Pekanbaru City, it is known that from months October to November 2019 were 60 deliveries, there were 23 people who participated in pregnancy exercise, where there was a degree II perineal rupture, namely 7 people and no perineal rupture occurred as many as 11 and 5 people had not given birth. This study aims to determine the relationship between pregnancy exercise and perinium rupture during delivery at PMB Dince Safrina Pekanbaru in 2020. This type of research is quantitative with a cross-sectional study approach. Sampling in this study using non random sampling technique with purposive sampling. The population in this study were 35 mothers giving birth at PMB Dince Syafrina. The analysis used The analysis used was univariate and bivariate. The results showed there was a relationship between pregnancy exercise and perineal rupture at delivery. It is hoped that the Independent Practice of Midwife Dince Syafrina, SST will be able to formulate ways to prevent perineal rupture during childbirth, namely by encouraging mothers to do pregnancy exercise and forming a class for pregnant women to teach pregnant women so that they are better prepared for childbirth.